High-connectivity-porosity SiO2 / HA composite ceramic artificial bone material and preparation method thereof

By using template pretreatment and gradient calcination processes, a SiO2/HA composite ceramic material with high interconnected porosity was prepared, which solved the problems of brittleness and poor pore connectivity of HA ceramic materials and optimized the mechanical properties and pore structure of the material.

CN121449415APending Publication Date: 2026-02-03NANJING STOMATOLOGICAL HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511631261.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing HA ceramic materials are brittle, have low fracture toughness, low porosity and poor connectivity, making them difficult to withstand mechanical loads under physiological conditions. Furthermore, traditional composite processes cannot simultaneously optimize the mechanical properties and pore structure of the materials.

Method used

By employing a process of template pretreatment, precise compounding, and gradient calcination, and through SiO2@PAA micelle template design and surfactant modification, a connected pore structure is formed, which enhances the mechanical properties and porosity of HA, avoids SiO2 agglomeration, and achieves close compounding of SiO2 and HA.

Benefits of technology

A SiO2/HA composite ceramic material with high interconnected porosity was achieved, which improved the mechanical properties and pore structure stability of the material, provided space for bone tissue ingrowth and nutrient transport, and solved the problems of brittleness and uneven pore distribution in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121449415A_ABST
    Figure CN121449415A_ABST
Patent Text Reader

Abstract

The invention discloses a high-connectivity porosity SiO2 / HA composite ceramic artificial bone material and a preparation method thereof, and belongs to the technical field of ceramic material preparation. The method adopts a synergistic process of template pretreatment, precise compounding and gradient calcination, and comprises the following steps: preparing SiO2 (at) PAA micelle particles, carrying out synergistic modification on the SiO2 (at) PAA micelle particles by SDS and Tween 80, mixing the SiO2 (at) PAA micelle particles with HA powder, regulating and controlling the stirring speed to prepare composite slurry, and carrying out gradient calcination to obtain the product. Regulating and controlling by ammonia water to enable SiO2 to form a broken cavity structure, and constructing a high-connectivity pore network; the double surfactants avoid particle aggregation, and low-speed stirring ensures the pore-forming effect. The material has high connectivity porosity and excellent mechanical properties, HA and an open pore SiO2 interface are tightly combined, bone tissue ingrowth and substance transmission can be promoted, the problems that a traditional HA material is large in brittleness, poor in pore connectivity, SiO2 agglomeration and the like are solved, the process is simple and controllable, and the material is suitable for large-scale production and scenes such as load-bearing bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of ceramic material preparation, and particularly relates to a high-connective-porosity SiO2 / HA composite ceramic artificial bone material and a preparation method thereof. BACKGROUND

[0002] Hydroxyapatite (HA) has excellent biocompatibility, bioactivity and bone conduction due to its high similarity to the chemical composition and crystal structure of natural bone mineral of human body, and is a commonly used ceramic artificial bone repair material in clinical practice. However, pure HA ceramic has inherent defects: high brittleness, low fracture toughness, difficult to withstand mechanical load in physiological environment; low porosity, isolated pores and poor connectivity, which cannot provide sufficient space for bone tissue growth and is not conducive to nutrient transport and metabolic waste discharge; at the same time, the mechanical properties of single HA phase are low in matching degree with natural bone tissue, which limits its application in load-bearing bone repair and other scenarios.

[0003] In order to improve the performance of HA, the existing technology often adopts composite modification or pore-forming process. In terms of pore-forming, common pore-forming agents include high molecular polymers and carbon powder, but the pore size formed by carbon powder is uneven and distributed randomly, which seriously affects the mechanical strength of the material; organic polymers (such as polyvinyl alcohol and polyethylene glycol) have poor compatibility with HA precursor solution, and are prone to agglomeration and delamination, resulting in uneven pore distribution and poor structural stability. In terms of composite modification, some studies introduce SiO2 to improve the mechanical properties, but SiO2 is prone to agglomeration in traditional composite process, and the interface between SiO2 and HA is not tight, and the pore structure cannot be optimized simultaneously, so it is difficult to balance the mechanical properties of the material.

[0004] Therefore, it is a key to develop a ceramic artificial bone material with high-connective-porosity and excellent mechanical properties to solve the bottleneck of the existing technology. SUMMARY

[0005] The application aims to overcome the shortcomings of the prior art and provide a high-connective-porosity SiO2 / HA composite ceramic artificial bone material and a preparation method thereof. Through the synergistic process of template pretreatment, precise compounding and gradient calcination, the problems of poor compatibility between pore-forming agent and HA precursor, SiO2 agglomeration and low porosity are solved, and a ceramic artificial bone material with optimized mechanical properties is obtained.

[0006] To achieve the above-mentioned purpose, the application provides the following technical scheme:

[0007] A preparation method of a high-connective-porosity SiO2 / HA composite ceramic artificial bone material, the operation steps are as follows:

[0008] S1. Template pretreatment and micelle preparation: 0.2-0.3 g of polyacrylic acid (PAA, MV=3000) was dissolved in 5-7 mL of ammonia water and 2-3 mL of deionized water was added, stirred for 5-10 min, then it was added dropwise into 60-80 mL of anhydrous ethanol, after the dropwise addition was completed, it was stirred for 1-2 h, then 2-3 mL of tetraethyl orthosilicate (TEOS) was added, after the dropwise addition was completed, the reaction was continued for 4-6 h, to obtain a SiO2@PAA micelle suspension, and SiO2@PAA microparticle was obtained by centrifugation;

[0009] S2. Particle surface modification: the SiO2@PAA microparticles in step S1 were dispersed in 10 mL of anhydrous ethanol, 0.1 g of sodium dodecyl sulfate (SDS) and 0.1 g of Tween 80 were added, and ultrasonic mixing was performed for 5-10 min to obtain a modified SiO2@PAA microparticle dispersion;

[0010] S3. 3-5 g of hydroxyapatite powder (HA) was added to the dispersion in step S2, and 30-50 mL of anhydrous ethanol was added, and stirred at 600-800 r / min for 20-30 min, then the stirring speed was reduced to 50-100 r / min, and 40-50 mL of deionized water was added, and the anhydrous ethanol was volatilized by heating to 60-80°C, to obtain a uniform composite slurry;

[0011] S4. Shaping and preliminary calcination: the composite slurry was poured into a crucible, and was placed at room temperature for 12-24 h, then was placed in a muffle furnace, and was heated at a rate of 3-5°C / min to 400-500°C, and was kept for 2-3 h to make the PAA template completely gasify and remove, and after cooling, a porous intermediate was obtained; then the temperature was continued to be raised at a rate of 5-7°C / min to 1100-1200°C, and was kept for 3-4 h, and was naturally cooled to room temperature, to obtain a ceramic artificial bone material.

[0012] In step S1, the amount of ammonia water in the raw material ratio for synthesizing SiO2@PAA micelles is important, ammonia water catalyzes the formation of SiO2 from TEOS, when the amount of ammonia water increases, the reaction rate is too fast, so that SiO2 cannot form a uniform spherical shell outside the PAA micelles, and after removing the PAA template, SiO2 is a broken cavity structure. This structure can provide a connected pore structure and enhance the mechanical properties of the artificial bone material.

[0013] SiO2@PAA micelles are synthesized and mixed with HA, SiO2 can enhance the mechanical properties of HA, and PAA can increase the porosity of the artificial bone material during the heating process.

[0014] In step S2, SDS is an anionic surfactant, and Tween 80 is a non-ionic surfactant. SDS realizes the preliminary dispersion of SiO2@PAA micelle particles through electrostatic repulsion; the long chain of the non-ionic surfactant provides a steric hindrance effect, further enhancing the stability of the dispersion liquid, and particle aggregation provides conditions for subsequent dispersion.

[0015] In step S3, after the addition of deionized water, the stirring speed needs to be reduced to 50-100 r / min, because PAA is dissolved in water, and fast stirring will cause the SiO2-coated PAA micelles to dissolve, thereby losing the pore-forming performance.

[0016] According to the preparation method, a high-connected porosity SiO2 / HA composite ceramic artificial bone material is obtained.

[0017] The beneficial effects of the present application compared with the prior art

[0018] (1) Pore structure optimization: through SiO2@PAA micelle template design and precise calcination process, the open-pore SiO2 formed after the gasification of PAA constructs a porous network with excellent connectivity and uniform size, and the open-pore structure can directly promote pore penetration, and provide sufficient space for bone tissue ingrowth, nutrient transmission and metabolic waste discharge, solving the problem of isolated and chaotic distribution of pores caused by traditional pore-forming agents.

[0019] (2) Synergistic improvement of mechanical properties and compatibility: open-pore SiO2 and HA form a close composite structure, which on the one hand improves the brittleness defect of pure HA ceramic through structural support, and on the other hand HA can penetrate into the pores of open-pore SiO2, significantly reducing the interface incompatibility between the two, and steadily improving the mechanical properties of the artificial bone material.

[0020] (3) Enhanced dispersion stability: through the synergistic surface modification of SDS and Tween 80, the electrostatic repulsion and steric hindrance effect are utilized to avoid the agglomeration of SiO2@PAA micelles and HA particles, ensuring the uniformity of the composite slurry and guaranteeing the structural consistency and performance stability of the material.

[0021] (4) Efficient and controllable process: the preparation process does not require complex equipment, and through precise control of raw material ratio and heating rate, the optimization of pore connectivity, the enhancement of mechanical properties and the improvement of compatibility are realized simultaneously, the process has good repeatability, is suitable for large-scale production, and solves the technical bottleneck that traditional composite processes cannot simultaneously consider porosity, mechanical properties and compatibility. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 is a scanning electron microscope picture of the ceramic artificial bone material prepared in Example 1;

[0023] Figure 2(a)-(b) are transmission electron microscope photos of SiO2@PAA micellar particles and modified SiO2@PAA micellar particles prepared in Example 1, respectively;

[0024] Figure 3 (a)-(b) are transmission electron microscope photos of SiO2@PAA micellar particles and modified SiO2@PAA micellar particles prepared in Example 1, respectively;

[0025] Figure 4 is a point scanning energy spectrum of the ceramic artificial bone material prepared in Example 1;

[0026] Figure 5 is an XRD spectrum of the ceramic artificial bone material prepared in Examples 1-3;

[0027] Figure 6 is a nitrogen adsorption desorption curve of Example 1 and Comparative Examples 1-4;

[0028] Figure 7 is a strain strain curve of Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0029] In order to make the above objectives, features and advantages of the present application more apparent and easy to understand, the specific embodiments of the present application will be described in detail below. The following content is only an example and description of the concept of the present application, and those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways instead, as long as they do not deviate from the concept of the present application, which shall belong to the protection scope of the present application.

[0030] The above preparation method of the present application will be described below through specific examples and comparative examples.

[0031] Example 1

[0032] A preparation method of a high-connected porosity SiO2 / HA composite ceramic artificial bone material, comprising the following steps:

[0033] S1. Template pretreatment and micelle preparation: 0.2 g of PAA (MV=3000) is dissolved in 5 mL of ammonia water, 2 mL of deionized water is added, stirred for 5 min, then slowly added into 60 mL of anhydrous ethanol, and after the addition is completed, continue to stir for 1 h, then add 2 mL of TEOS dropwise, after the addition is completed, constant temperature reaction for 4 h, and obtain SiO2@PAA micellar particles by centrifugal separation;

[0034] S2. Particle surface modification: the SiO2@PAA micellar particles described above are dispersed in 10 mL of anhydrous ethanol, 0.1 g of SDS and 0.1 g of Tween 80 are added, and ultrasonic mixing is performed for 5 min to obtain a uniform modified SiO2@PAA micellar particle dispersion;

[0035] S3. Composite slurry preparation: 3 g of HA powder is added to the modified dispersion described above, 30 mL of anhydrous ethanol is supplemented, stirring is performed at a speed of 600 r / min for 20 min, then the stirring speed is reduced to 50 r / min, 40 mL of deionized water is slowly added, heating is performed to 60°C and the temperature is maintained until the anhydrous ethanol is completely volatilized, and a uniform composite slurry is obtained;

[0036] S4. Shaping and calcination: the composite slurry is poured into a pre-dried crucible, is left to solidify at room temperature for 12 h, then the crucible is placed in a muffle furnace, heating is performed to 400°C at a heating rate of 3°C / min, the temperature is maintained for 2 h to completely gasify and remove the PAA template, and natural cooling is performed to room temperature to obtain a porous intermediate; heating is then performed to 1100°C at a heating rate of 5°C / min, the temperature is maintained for 3 h, and natural cooling is performed to room temperature, and finally a ceramic artificial bone material is obtained.

[0037] Example 2

[0038] A method for preparing a high-connected porosity SiO2 / HA composite ceramic artificial bone material, comprising the following steps:

[0039] S1. Template pretreatment and micelle preparation: 0.25 g of PAA (MV=3000) is dissolved in 6 mL of ammonia water, 2.5 mL of deionized water is added, stirring is performed for 8 min, then 70 mL of anhydrous ethanol is slowly added dropwise, stirring is continued for 1.5 h after the dropwise addition is completed, 2.5 mL of TEOS is added dropwise, constant temperature reaction is performed for 5 h after the dropwise addition is completed, and SiO2@PAA micellar particles are obtained by centrifugal separation;

[0040] S2. Particle surface modification: the SiO2@PAA micellar particles described above are dispersed in 10 mL of anhydrous ethanol, 0.1 g of SDS and 0.1 g of Tween 80 are added, and ultrasonic mixing is performed for 8 min to obtain a uniform modified SiO2@PAA micellar particle dispersion;

[0041] S3. Composite slurry preparation: 4 g of HA powder is added to the modified dispersion described above, 40 mL of anhydrous ethanol is supplemented, stirring is performed at a speed of 700 r / min for 25 min, then the stirring speed is reduced to 80 r / min, 45 mL of deionized water is slowly added, heating is performed to 70°C and the temperature is maintained until the anhydrous ethanol is completely volatilized, and a uniform composite slurry is obtained;

[0042] S4. Forming and calcination: pour the composite slurry into a pre-dried crucible, stand for solidification at room temperature for 18 h, then place the crucible in a muffle furnace, heat to 450℃ at a heating rate of 4℃ / min, keep for 2.5 h to completely gasify and remove the PAA template, naturally cool to room temperature to obtain a porous intermediate; then heat to 1150℃ at a heating rate of 6℃ / min, keep for 3.5 h, naturally cool to room temperature, and finally obtain a ceramic artificial bone material.

[0043] Example 3

[0044] A preparation method of a high-connected porosity SiO2 / HA composite ceramic artificial bone material, comprising the following steps:

[0045] S1. Template pretreatment and micelle preparation: dissolve 0.3 g of PAA (MV=3000) in 7 mL of ammonia water, add 3 mL of deionized water, stir for 10 min, then slowly drop 80 mL of anhydrous ethanol, continue to stir for 2 h after dropping, then drop 3 mL of TEOS, and react for 6 h at constant temperature after dropping, and obtain SiO2@PAA micelle particles by centrifugal separation;

[0046] S2. Particle surface modification: disperse the above SiO2@PAA micelle particles in 10 mL of anhydrous ethanol, add 0.1 g of SDS and 0.1 g of Tween 80, and ultrasonically mix for 10 min to obtain a uniform modified SiO2@PAA micelle particle dispersion;

[0047] S3. Composite slurry preparation: add 5 g of HA powder to the above modified dispersion, supplement 50 mL of anhydrous ethanol, stir at a speed of 800 r / min for 30 min, then reduce the stirring speed to 100 r / min, slowly add 50 mL of deionized water, heat to 80℃ and keep, until the anhydrous ethanol is completely volatilized, and a uniform composite slurry is obtained;

[0048] S4. Forming and calcination: pour the composite slurry into a pre-dried crucible, stand for solidification at room temperature for 18 h, then place the crucible in a muffle furnace, heat to 450℃ at a heating rate of 4℃ / min, keep for 2.5 h to completely gasify and remove the PAA template, naturally cool to room temperature to obtain a porous intermediate; then heat to 1150℃ at a heating rate of 6℃ / min, keep for 3.5 h, naturally cool to room temperature, and finally obtain a ceramic artificial bone material.

[0049] Comparative Example 1

[0050] Directly take 3 g of HA powder, add 30 mL of deionized water, stir uniformly, then pour into a pre-dried crucible, stand at room temperature for 12 h, then place the crucible in a muffle furnace, heat to 1100℃ at a heating rate of 5℃ / min, keep for 3 h, and naturally cool to room temperature to obtain a pure HA ceramic material.

[0051] Comparative Example 2

[0052] S1. Template pretreatment and micelle preparation: the operation is completely consistent with that of Example 1;

[0053] S2. Disperse the SiO2@PAA micelle particles in 10 mL of anhydrous ethanol to obtain a dispersion;

[0054] S3. Composite slurry preparation: the operation is completely consistent with that of Example 1;

[0055] S4. Molding and calcination: the operation is completely consistent with that of Example 1.

[0056] Comparative Example 3

[0057] The difference from Example 1 is that the amount of ammonia water added in step S1 is 3 mL, and the remaining steps are the same as those of Example 1.

[0058] Comparative Example 4

[0059] The difference from Example 1 is that in step S3, the stirring speed is always 600 r / min, and the remaining steps are the same as those of Example 1.

[0060] Figure 1 is a scanning electron microscope picture of the ceramic artificial bone material prepared in Example 1; it can be seen from the picture that there is a uniform distribution of through-hole network, without isolated pores or chaotic distribution, which directly proves that the present application solves the core defects of poor pore connectivity and uneven distribution caused by traditional pore-forming agents through SiO2@PAA micelle template and calcination.

[0061] Figure 2 (a)-(b) are transmission electron microscope pictures of SiO2@PAA micelle particles and modified SiO2@PAA micelle particles prepared in Example 1, respectively; Figure 2 (a) (unmodified) micelle particles exist in light agglomeration, Figure 2 (b) (SDS+Tween 80 modified) particles are in a monodisperse state, which proves the effectiveness of the double surfactant cooperative modification, realizing uniform dispersion of particles through electrostatic repulsion + steric hindrance effect, and ensuring the uniformity of the subsequent composite slurry.

[0062] Figure 3(a)-(b) are transmission electron micrographs of SiO2@PAA micelles particles prepared in Example 1 after stirring in deionized water at 50 r / min and 600 r / min, respectively; Figure 3 (a) (50 r / min low-speed stirring) micelles remain intact core-shell structure, Figure 3 (b) (600 r / min high-speed stirring) only open-pore SiO2 particles remain, proving the key design of reducing stirring speed in step S3 to avoid premature dissolution of PAA and loss of pore-forming performance. In addition, it can be seen that the SiO2 particles are open-pore structures, which can allow HA to enter the cavities and also play a role in connecting the overall porosity.

[0063] Figure 4 is the point scanning energy spectrum of the artificial bone material prepared in Example 1; the Ca and P elements of HA and the Si and O elements of SiO2 are detected in the energy spectrum.

[0064] Figure 5 is the XRD spectrum of the artificial bone material prepared in Examples 1-3; in the XRD spectra of Examples 1-3, only the characteristic peaks of HA and amorphous SiO2 appear, no impurity phase is generated, proving that the composite process does not destroy the biological activity crystal structure of HA, and the composite of SiO2 and HA does not cause adverse reactions, ensuring the biological compatibility of the material.

[0065] Figure 6 is the nitrogen adsorption desorption curve of Example 1 and Comparative Examples 1-4; it can be seen that the porosity of Example 1 is significantly higher than that of Comparative Example 1 pure HA, and there is almost no adsorption capacity; in Comparative Example 2, SiO2 agglomerates, resulting in low porosity; in Comparative Example 3, the amount of ammonia water is insufficient, the micelle structure is incomplete, and the adsorption capacity is low; in Comparative Example 4, high-speed stirring causes PAA to dissolve prematurely, and the pore-forming effect fails, resulting in low porosity, which proves the high interconnected porosity advantage of the material of the present application.

[0066] Figure 7 is the strain-strain curve of Example 1 and Comparative Examples 1-3; the peak strength and fracture strain of the curve of Example 1 are significantly higher than those of Comparative Example 1 (pure HA, brittle fracture, low peak value), Comparative Example 2 (unmodified micelles, agglomeration leading to uneven mechanical properties), and Comparative Example 3 (incomplete pore structure, insufficient support), proving that the structural support of open-pore SiO2 + the close composite of HA and SiO2 effectively improves the brittle defect of pure HA, achieving a synergistic improvement in mechanical properties and porosity.

Claims

1. A method for preparing a high-interconnected porosity SiO2 / HA composite ceramic artificial bone material, characterized in that, The method comprises the following steps: S1. Template pretreatment and micelle preparation: PAA, MV=3000, is dissolved in ammonia water, and then added dropwise into anhydrous ethanol after stirring with deionized water, and TEOS is added after continuous stirring, and centrifuged after reaction to obtain SiO2@PAA micelle particles; S2. Particle surface modification: the SiO2@PAA micelle particles obtained in step S1 are dispersed in anhydrous ethanol, and SDS and Tween 80 are added, and ultrasonic mixing is performed to obtain a modified SiO2@PAA micelle particle dispersion liquid; S3. Composite slurry preparation: HA powder is added to the dispersion liquid of step S2, anhydrous ethanol is supplemented, and stirring is performed at 600-800 r / min, and then the stirring speed is reduced to 50-100 r / min, deionized water is added, and anhydrous ethanol is volatilized by heating to obtain a uniform composite slurry; S4. Shaping and gradient calcination: the composite slurry is cured at room temperature, and is placed in a muffle furnace, and is heated at a rate of 3-5 ℃ / min to 400-500 ℃ to remove the PAA template, and is cooled to obtain a porous intermediate; and then heated at a rate of 5-7 ℃ / min to 1100-1200 ℃, and is naturally cooled to room temperature to obtain a ceramic artificial bone material.

2. The production method according to claim 1, characterized by, The amount of each raw material in step S1 is: polyacrylic acid 0.2-0.3 g, ammonia water 5-7 mL, deionized water 2-3 mL, anhydrous ethanol 60-80 mL, and tetraethyl orthosilicate 2-3 mL.

3. The preparation method according to claim 1, characterized in that, The time parameters of each stage in step S1 are: stirring time after adding deionized water 5-10 min, stirring time in anhydrous ethanol 1-2 h, and tetraethyl orthosilicate reaction time 4-6 h.

4. The method of claim 1, wherein, The parameters in step S2 are: the amount of anhydrous ethanol used for dispersion is 10 mL, the amount of SDS is 0.1 g, the amount of Tween 80 is 0.1 g, and the ultrasonic mixing time is 5-10 min.

5. The preparation method according to claim 1, characterized in that, The amount and temperature parameters of each material in step S3 are: HA powder 3-5 g, supplemented anhydrous ethanol 30-50 mL, deionized water 40-50 mL, and heating temperature 60-80 ℃.

6. The method of claim 1, wherein, The stirring time at 600-800 r / min in step S3 is 20-30 min.

7. The preparation method according to claim 1, characterized in that, The time parameters in step S4 are: room temperature curing time 12-24 h, 400-500 ℃ holding time 2-3 h, and 1100-1200 ℃ holding time 3-4 h.

8. The high-interconnected-porosity SiO2 / HA composite ceramic artificial bone material prepared according to the preparation method of any one of claims 1-7, characterized in that, The material has a connected porous network constructed by SiO2, and a close composite structure is formed between HA and open-pore SiO2.